2019
DOI: 10.4103/1735-5362.258488
|View full text |Cite
|
Sign up to set email alerts
|

β-lactoglobulin-irinotecan inclusion complex as a new targeted nanocarrier for colorectal cancer cells

Abstract: Beta-lactoglobulin (β-LG) is a lipocalin family member whose general function appears to be solubilizing and transport of hydrophobic molecules. Some properties such as avalability, ease of purification, and peculiar resistance to acidic environments can make β-LG as a carrier for hydrophobic and acid labile drugs for oral administration. In this protein vehicle, drug could be protected in acidic environment of stomach and then released within the basic small intestine. In this study, the potential of β-LG as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Since HSPGs are ubiquitously expressed by most mammalian cell types, such heparin-binding lipocalins may enter numerous cells. This finding is of special interest as BLG has been recently used as a nanocarrier for delivering biological agents such as chemotherapeutics (Bijari et al 2019;Shafaei et al 2017), and has also been attributed cytoproliferative effects (Tai et al 2016). In addition, it was demonstrated that antigens with inherent heparin-binding affinity are supported more efficiently by the immune system (Léonetti et al 2010), an effect which might shed some light on the enigmatic allergenicity of lipocalins.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Since HSPGs are ubiquitously expressed by most mammalian cell types, such heparin-binding lipocalins may enter numerous cells. This finding is of special interest as BLG has been recently used as a nanocarrier for delivering biological agents such as chemotherapeutics (Bijari et al 2019;Shafaei et al 2017), and has also been attributed cytoproliferative effects (Tai et al 2016). In addition, it was demonstrated that antigens with inherent heparin-binding affinity are supported more efficiently by the immune system (Léonetti et al 2010), an effect which might shed some light on the enigmatic allergenicity of lipocalins.…”
Section: Discussionmentioning
confidence: 90%
“…Both lipocalins are relevant human allergens. In addition, BLG was demonstrated to be a potent stimulator of proliferation (Tai et al 2016) and is used as a nanocarrier for delivering pharmacological agents (Bijari et al 2019;Shafaei et al 2017). Therefore, in this work we aimed to identify cell surface components responsible for the cellular uptake of these lipocalins.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between atenolol and βcyclodextrin was observed by the FT-IR transmission spectrum of atenolol, β-cyclodextrin, and inclusion complex using the potassium bromide (KBr) disc technique 2,14 . All the spectrum acquired were scanned between 400 and 4000 cm -1 .…”
Section: Characterization Of Atenolol-β-cyclodextrin Inclusion Complementioning
confidence: 99%
“…The crystallographic state of atenolol, β-cyclodextrin, and an inclusion complex of atenolol-βcyclodextrin was investigated using X-ray diffractometer (Phillips) in the range 2Ө (5-50°) at room temperature 14 .…”
Section: Powder X-ray Diffraction (Xrd)mentioning
confidence: 99%
See 1 more Smart Citation